The best American essays 2023 - Gornick, Vivian; Atwan, Robert; Alfaro, Ciara; Barnet, Jillian; Baumgartel, Sylvie; Borsuk, Eric; Dennis, Chris, 1979-; Eberlein, Xujun; Eliason, Sandra Hager; Estreich, George; Gerber, Merrill Joan; Gwartney, Debra; et al. (Best American series., 2023)
Presents a collection of the year's best essays as selected by author and critic Vivian Gornick.